Assessment of morphological and genomic variation in Attakkari rice for selection of blast-resistant lines - Kishanthan, A.; Terensan, S.; Gajapathy, K.; Antonyrajah, P. (Elsevier, 2025)
Traditional rice landraces remain vital for food security and cultural identity, yet their use in breeding is constrained by insufficient characterization. This study comprehensively evaluated Attakkari, a prominent local cultivar in Northern Sri Lanka, focusing on its genetic diversity, agronomic traits, and blast resistance potential. Farmer surveys (n = 119) revealed that Attakkari is highly valued for yield (2500–3150 kg/acre), favorable taste, grain quality, and strong local market demand, with 95.79 % reporting consistently high preference. Despite concerns of blast susceptibility noted by 65 % of farmers, cultivation persists due to adaptability and cultural significance. Morphological analysis of seed samples identified ten clusters based on grain traits, from which nine morphotypes were selected for further study. Image sensing using RGB and grayscale intensities differentiated subtle pericarp variations into four sub-groups. ITS sequencing confirmed high genetic similarity (98.5–100 %) among morphotypes, with some sequences showing 100 % similarity to Oryza nivara from South Korea, indicating possible contributions from wild progenitors. Screening for ten major blast resistance genes revealed considerable variation; notably, Att 44, Att 06, and Att 16 carried up to nine resistance genes (Pita/Pita-2, Piz, Pizt, Pik, Pikh, Pib, Pikp, Pi1, Pi5, Pikm). Field evaluations highlighted significant agronomic diversity, with Att 94, Att 44, and Att 116 exhibiting superior vigor, yield components, and grain weight compared to reference varieties (RY, RM, Co 10). Overall, this integrated morphological, molecular, and agronomic assessment demonstrates Attakkari's strong potential for breeding programs aimed at enhancing yield, blast resistance, and sustainable rice production in Northern Sri Lanka.
Keywords: Paddy yield trends; Statistical analysis; Irrigation schemes; Agricultural policy; Open data; Northern Sri Lanka